Improving the purification process for aqueous-alcoholic solutions by shuhgіte - Melnyk, Lyudmila; Krivorotko, Volodimir (My University, 2012)
The process of purification of water-alcohol solutions shungita of contaminants that degrade the quality indicators of vodkas. Found that shungite adsorbent natural origin better absorb aldehydes, higher alcohols, methanol. The substantiation of the mechanism of sorption.
Keywords: adsorption; aldehydes; hydroalcoholic solutions; higher alcohols; methanol; адсорбція; альдегіди; водно-спиртові розчини; вищі спирти; метанол; кафедра процесів і апаратів харчових виробництв; кафедра теоретичної механіки та ресурсоощадних технологій